The Status and Future of Small Uncrewed Aircraft Systems (UAS) in Operational Meteorology - Pinto, James O.; O’Sullivan, Debbie; Taylor, Stewart; Elston, Jack; Baker, C. B.; Hotz, David; Marshall, Curtis; Jacob, Jamey; Barfuss, Konrad; Piguet, Bruno; Roberts, Greg; Omanovic, Nadja; et al. (Bulletin of the American Meteorological Society, 2021)
The boundary layer plays a critical role in regulating energy and moisture exchange between the surface and the free atmosphere. However, the boundary layer and lower atmosphere (including shallow flow features and horizontal gradients that influence local weather) are not sampled at time and space scales needed to improve mesoscale analyses that are used to drive short-term model predictions of impactful weather. These data gaps are exasperated in remote and less developed parts of the world where relatively cheap observational capabilities could help immensely. The continued development of small, weather-sensing uncrewed aircraft systems (UAS), coupled with the emergence of an entirely new commercial sector focused on UAS applications, has created novel opportunities for partially filling this observational gap. This article provides an overview of the current level of readiness of small UAS for routinely sensing the lower atmosphere in support of national meteorological and hydrological services (NMHS) around the world. The potential benefits of UAS observations in operational weather forecasting and numerical weather prediction are discussed, as are key considerations that will need to be addressed before their widespread adoption. Finally, potential pathways for implementation of weather-sensing UAS into operations, which hinge on their successful demonstration within collaborative, multi-agency-sponsored testbeds, are suggested.